Investigation of cell parameters, microstructures and electrochemical behaviour of LiMn(2)O(4) normal and nano powders - Kamarulzaman, N.; Yusoff, R.; Kamarudin, N.; Shaari, N.H.; Aziz, N.A.A.; Bustam, M.A.; Blagojevic, N.; Elcombe, M.; Blackford, M.; Avdeev, M.; Arof, Abdul Kariem (Elsevier, 2009)
Nano materials are usually difficult to prepare. This work presents a simple way of preparing LiMn(2)O(4) nano powders using the high-energy ball milling method. This method has the advantage of producing pure, single-phase and crystalline nano powders. The milling method is carefully controlled to avoid unwanted chemical reactions that may change the stoichiometry of the material. Nano powders of between 30 and 50 nm are obtained. Structural studies of the nano powders, as well as the more-conventional micron-sized LiMn(2)O(4), are made using X-ray diffraction and neutron diffraction methods. Electrochemical evaluation of the materials is undertaken with a three-probe cyclic voltammetry technique and galvanostatic charge-discharge measurements. Structural studies reveal that not only are the crystallites of the nano powders much reduced in size from the normal powders, but their cell parameters are also smaller. The performance characteristics of the nano material show an improvement over that of the micron-sized material by about 17 in the 1st cycle and 70.6 in the 5th cycle, at which the capacity is 132 mAh g(-1). The normal material suffers from severe capacity fading but the nano material shows much improved capacity retention.